2002
DOI: 10.1016/s0092-8674(02)00649-9
|View full text |Cite
|
Sign up to set email alerts
|

The Ribosomal Exit Tunnel Functions as a Discriminating Gate

Abstract: Translation of SecM stalls unless its N-terminal part is "pulled" by the protein export machinery. Here we show that the sequence motif FXXXXWIXXXXGIRAGP that includes a specific arrest point (Pro) causes elongation arrest within the ribosome. Mutations that bypass the elongation arrest were isolated in 23S rRNA and L22 r protein. Such suppressor mutations occurred at a few specific residues of these components, which all face the narrowest constriction of the ribosomal exit tunnel. Thus, we suggest that this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

27
629
2
10

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 514 publications
(668 citation statements)
references
References 26 publications
27
629
2
10
Order By: Relevance
“…SecM arrest sequence, upon its translation interacts with the ribosomal proteins L4 and L22 as well as 23S rRNA in the ribosomal tunnel 7,8 . A number of critical residues, constituting the SecM arrest motif, FXXXXWIXXXXGIRAGP 7 (in bold type) are of immense importance, ensuring the efficiency of the translational arrest.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…SecM arrest sequence, upon its translation interacts with the ribosomal proteins L4 and L22 as well as 23S rRNA in the ribosomal tunnel 7,8 . A number of critical residues, constituting the SecM arrest motif, FXXXXWIXXXXGIRAGP 7 (in bold type) are of immense importance, ensuring the efficiency of the translational arrest.…”
Section: Discussionmentioning
confidence: 99%
“…A number of critical residues, constituting the SecM arrest motif, FXXXXWIXXXXGIRAGP 7 (in bold type) are of immense importance, ensuring the efficiency of the translational arrest. Mutations, or deletions of these critical residues may lead to the relief of the translation elongation arrest 7,8 . Thus, maintaining the sequence of the SecM arrest motif FXXXXWIXXXXGIRAGP 7 intact is absolutely critical to ensure that the protein under study would remain stably bound to the ribosome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of nascent peptides interact with the exit tunnel and stall elongation at specific sites within their peptide chain. The tunnel constriction has also been implicated in peptide-mediated pausing (Nakatogawa and Ito, 2002;Cruz-Vera et al, 2005). Previous research had indicated that in bacteria, mutations in RPL22 and RPL4 mediate erythromycin resistance by perturbing the conformation of rRNA, and a variety of changes in these proteins could mediate macrolide resistance (Gregory and Dahlberg, 1999;Gabashvili et al, 2001;Zaman et al, 2007;Caldwell et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…RPL22 and RPL4 form a constriction that results in the narrowest passage in the tunnel. This exit tunnel interacts with nascent translation products and functions as a discriminating gate and may control the nascent chain elongation (Nakatogawa and Ito, 2002;Berisio et al, 2003). But the correlation between the function of RPL22 and insecticide resistance has not been reported.…”
Section: Introductionmentioning
confidence: 99%